Feature, experimental radio drama and radio experiment analyzed with Edmund Feldman’s critical method - Kowalska-Elkader, Natalia (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter analyzes radio works using Feldman's critical method in adaptation to the ground of audio works. In order to fully reflect its assumptions, as well as the variety of artistic radio forms, three programs of different genres are analyzed: the experimental radio drama Shell Shock by Tomasz Plata, the artistic radio documentary There is Something Behind Every Door by Joanna Dąbrowska-Zadrowska and Witold Zadrowski and the radio experiment 86400 Seconds Time Zones by Chantal Dumas .